Atlases: Reasons for Their Creation and First Concepts - Krakovskyi, S. P. (Ukrainian Geographical Journal, 2024)
Atlas cartography in the 21st century is losing its “flagship” status. Paper atlases have become less attractive in the age of information society. At the same time, electronic atlases either lose out to other cartographic applications or dissolve among them, losing their unique features. To find ideas and meanings for new EA concepts, we explored the history of the first atlases to understand their essence, reasons for creation, and success factors. The article, based on contemporary works by historians of cartography and cultural geographers, clarifies the answers to the following questions: 1) What is the origin of the word “atlas”? Who was the first to use this word to describe a “collection of maps”? 2) Which atlas should be considered the first, particularly the first in the modern sense? Who originated the idea of the first atlas? 3) What was the atlas “Theatrum Orbis Terrarum” concept by A. Ortelius? 4) What was the concept of G. Mercator’s “Atlas sive Cosmographicæ Meditationes De Fabrica Mundi Et Fabricati Figura”?
Keywords: atlas; digital atlas; atlas cartography; history of cartography